2024
DOI: 10.3390/fib12030024
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Recycled High-Density Polyethylene Fibers on the Mechanical and Electrochemical Properties of Reinforced Concrete

Alejandro Flores Nicolás,
Elsa C. Menchaca Campos,
Mario Flores Nicolás
et al.

Abstract: The quantity of different plastics generated after consumption is an impact factor affecting the environment, and the lack of recycling generates solid waste. The purpose of this work is to incorporate high-density recycled polyethylene fibers (HDPE) for possible use as concrete reinforcement. Physical and mechanical properties from recycled fibers were analyzed, such as density, absorption, and stress resistance, as well as workability, air content, porosity, concrete compression, and flexural strength proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 95 publications
0
4
0
Order By: Relevance
“…The slump test is used to evaluate the consistency or workability of the concrete mix. The workability is an indicator of quality control of materials such as fine and coarse aggregates with the cementitious matrix [4]. Workability concrete results are shown in Figure 9 where the concrete control presents a 14 cm slump effect, and when adding treated natural fibers (TNF) an annealing increase due to the reduction in water quantity was obtained, and a consequence of UEO acting as a water reducer during the curing process, and the increase in a slump from high contents of SO3 in UEO [35,57].…”
Section: Physical Properties Of Fiber-reinforced Concretementioning
confidence: 99%
See 1 more Smart Citation
“…The slump test is used to evaluate the consistency or workability of the concrete mix. The workability is an indicator of quality control of materials such as fine and coarse aggregates with the cementitious matrix [4]. Workability concrete results are shown in Figure 9 where the concrete control presents a 14 cm slump effect, and when adding treated natural fibers (TNF) an annealing increase due to the reduction in water quantity was obtained, and a consequence of UEO acting as a water reducer during the curing process, and the increase in a slump from high contents of SO3 in UEO [35,57].…”
Section: Physical Properties Of Fiber-reinforced Concretementioning
confidence: 99%
“…[3]. To reduce the effects of corrosion, the need to obtain synthetic, natural, or waste materials as alternatives to conventional reinforced concrete has been sought [4].…”
Section: Introductionmentioning
confidence: 99%
“…Lightweight fibers can help in achieving lighter concrete structures, which can be beneficial for applications where weight reduction is desirable, such as in precast elements or structures with weight limitations. Alejandro Flores Nicolás et al [106] investigated the effect of high-density recycled polyethylene fiber on the mechanical properties of FRC. They found that the recycled fibers showed a decrease in tensile strength and toughness, but a slight 2.3% increase in concrete flexural strength.…”
Section: Densitymentioning
confidence: 99%
“…The incorporation of glass and polypropylene fibers on both the mechanical and microstructural characteristics of concrete has increased the crack resistance under the jet impact load [22,23]. The findings of the study offer valuable insights into the potential advantages of utilizing low-modulus elasticity fibers in enhancing the performance of concrete [24][25][26][27][28]. Henceforth, the nanoparticles influence the fresh, mechanical, and microstructural properties of concrete with the inclusion of supplementary cementitious material.…”
Section: Introductionmentioning
confidence: 99%